Optimized stiffness combination of a flexible-base hinged connector for very large floating structures. (July 2018) - Shi, Q.J.; Xu, D.L.; Zhang, H.C.; Zhao, H.; Wu, Y.S.
Abstract: Prototype design of a flexible connector indeed includes the aspects of stiffness arrangement, structural layout, strength analysis, fatigue analysis, and manufacturing constraints etc. This paper focuses on the stiffness design for the flexible-base hinged connector (FBHC). A three-modular platform is used for the case studies. How to layout the connector stiffness in different directions is very much interested in order to gain the most benefit in the reduction of the connector loads as well as module responses. An orthogonal experiment method is thus employed to examine the relationship between the stiffness combination and module responses. It is found that there is a dilemma to gain the both benefits on the minimum for connector load and relative displacement. By suitably relaxing the tolerance on displacement requirements, the optimal stiffness combination for the FBHC is suggested. In the comparison study with a rigid hinged connector (RHC), the FBHC can significantly reduce the connector loads with a confined flexibility. Highlights: A flexible-base hinged connector (FBHC) is modeled by the network modeling method. The effect of the stiffness combination of FBHC on module responses is studied. The optimal stiffness of FBHC is suggested based on orthogonal experiments. The FBHC can significantly reduce the connector loads with a confined flexibility.